STRATEGI ADAPTASI NELAYAN BAJO MENGHADAPI PERUBAHAN IKLIM: STUDI NELAYAN BAJO DI KABUPATEN SIKKA, FLORES, NUSA TENGGARA TIMUR - Nurlaili, Nurlaili (P2KK LIPI, 2012)
Climate change has a significant impact on coastal area ecosystem due to the rise of sea surface and its temperature, the change in salinity, and the frequency and intensity of extreme events such as tropical monsoons and high waves.Climate change has impacted social and economic activitiesin many areas. This paper aims to look at the adaptation strategy of Bajo fisherman in Sikka District East Nusa Tenggara province. The data for this study were collected by using in-depth interviews, observations and Focus Group Discussions. This research shows that Bajo fishermen develop adaptation strategy to face climate change through knowledge construction and innovation of fish capture. Keywords: adaptation strategy, climate change, knowledge construction, innovation